Pengaruh Kepemimpinan dan Kapabilitas Dinamis terhadap Manajemen Pengetahuan di Binus University Jakarta - Teguh Sriwidadi (Bina Nusantara University, 2014)
This research aims to analyze the effect of Leadership and Dynamic Capabilities on Knowledge Management at BINUS University. Research objects are lecturers and employees of BINUS Unversity with 90 respondents. Sampling technique used is disporporsiaonte stratified random sampling procedure, the number of subjects of each stratum would no be altered, while keeping the sample size unchanged. The data analysis method is IBM SPSS (Statistical Program for Social Science) version 20. The result is the effect of Leadership and Dynamic Capabilities on Knowledge Management presented by multiple regression equation: Y = 1,425 + 0,031 X1 + 0,625 X2, which Y = Knowledge Management, X1 = Leadership, and X2 = Dynamic Capabilities. The Dynamic Capabilities significantly affects Knowledge Management, but Leadership does not significantly affect Knowledge Management. Leadership variable has two functions, as Independent Variable but must be controlled and as the second Independent Variable or as Mediator.